Respostas

2014-05-18T19:21:58-03:00
Tenque aplicar forma de bascara -x=a 7x=b-12=c multiplica por um pois o a é  negativo
2014-05-18T19:28:28-03:00
-x²+7x-12=0     .(-1)

x
² - 7x + 12 = 0

a=1                      Δ=b²-4ac                        x= -b +/- √Δ
b= -7                    Δ= (- 7)² - 4.1.12                       2a
c= 12                   Δ= 49 - 48
                           Δ= 1                               x= -(-7) +/- √1
                                                                         2 . 1

                                                                x= +7 +/- 1
                                                                          2

                                                                X₁= 7 +1  ⇒ 8/2  =   4
                                                                         2                                                       
                                                                X₁₁= 7- 1 ⇒ 6/2 =  3
                                                                          2
2 5 2